Forensic discrimination of lipsticks using visible and attenuated total reflectance infrared spectroscopy. (May 2019) - Wong, Justina X.W.; Sauzier, Georgina; Lewis, Simon W.
Graphical abstract: Highlights: Forensic analysis of lipsticks often involves destructive techniques. Infrared and visible spectroscopy investigated as potential in situ approaches. 40 red- and nude-shaded lipsticks representing 20 brands examined. Chemometric data analysis successfully used for discrimination and identification. Abstract: Lipstick traces may be encountered in forensic investigations as traces left on clothing, drinkware, tissue papers or other surfaces. However, their probative value is limited by the discriminatory power and destructiveness of existing analysis schemes. This work employed analytical spectroscopy with chemometrics to provide objective and non-destructive characterisation of lipsticks for forensic purposes. 22 red-shaded and 18 nude-shaded lipsticks were analysed using visible absorbance and diffuse reflectance spectroscopy, as well as attenuated total reflectance Fourier transform infrared spectroscopy. Principal component analysis readily distinguished most samples based on their spectral profiles, with subsequent models yielding discrimination accuracies exceeding 94% for each spectroscopic mode. This could provide a greater level of confidence when conducting 'questioned versus known' comparisons of similar lipsticks. Further testing using external validation sets produced identification accuracies of 73–100 %, which may allow investigative leads to be more readily obtained from recovered lipstick traces.